The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/8926453
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination of Soils around a Hospital Waste Incinerator Bottom Ash Dumps Site

Abstract: Waste incineration is the main waste management strategy used in treating hospital waste in many developing countries. However, the release of dioxins, POPs, and heavy metals in fly and bottom ash poses environmental and public health concerns. To determine heavy metal (Hg, Pb, Cd, Cr, and Ag) in levels in incinerator bottom ash and soils 100 m around the incinerator bottom ash dump site, ash samples and surrounding soil samples were collected at 20 m, 40 m, 60 m, 80 m, 100 m, and 1,200 m from incinerator. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 15 publications
(15 reference statements)
2
17
1
1
Order By: Relevance
“…In general, emission readings obtained in this study from the ten different points in and around the medical waste incinerator for nitric oxide and ammonia was within the acceptable limits ≤0.06ppm. The readings obtained for hydrogen sulphide in front of the incinerator (0.07ppm) and main electrical station (0.06ppm) exceed the permitted limits and call be linked to construction materials used in the build [15]. Overall, incinerator in this study is functionally useful but could be improved via the integration of a multi-stage combustion chamber and scrubber which both aids in the mopping up of excess fumes as well as prompts complete combustion of waste at higher temperatures.…”
Section: Discussionmentioning
confidence: 79%
“…In general, emission readings obtained in this study from the ten different points in and around the medical waste incinerator for nitric oxide and ammonia was within the acceptable limits ≤0.06ppm. The readings obtained for hydrogen sulphide in front of the incinerator (0.07ppm) and main electrical station (0.06ppm) exceed the permitted limits and call be linked to construction materials used in the build [15]. Overall, incinerator in this study is functionally useful but could be improved via the integration of a multi-stage combustion chamber and scrubber which both aids in the mopping up of excess fumes as well as prompts complete combustion of waste at higher temperatures.…”
Section: Discussionmentioning
confidence: 79%
“…Within the urban ecosystem, soils are distinguished by composition and properties (Short et al, 1986). Natural landscapes are transformed into anthropogenic with a local change in biochemical cycles (accumulation and removal of chemical elements (Adama et al, 2016;Dymov et al, 2013). Urban soils, as a depositing component of the urban landscape, accumulate many trace elements, including heavy metals and metalloids, as well as organic compounds that are toxic to living organisms (Kicińska, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The 2011 Health Facility Research reported that one in three PHCs did not practice medical waste segregation, and of those who did, almost half reported burning their medical waste in the open area (NIHRD, 2012). These situations entail potential health risks to healthcare workers and community near the PHCs (Adama, Esena, Fosu-Mensah, & Yirenya-Tawiah, 2016;Oyekale & Oyekale, 2017;Udofia, Gulis, & Fobil, 2017). The exposed population increases as healthcare utilisation increases.…”
Section: Introductionmentioning
confidence: 99%